Do Singapore listed manufacturing firms follow pecking order theory? - Mardina Alycia, Marakus (Universiti Malaysia Sarawak (UNIMAS), 2011)
This study examines the determinants of Singapore listed manufacturing firms from 2005 until 2009. The main objective of this study is to examine the determinants of capital structure for Singapore listed manufacturing companies. The results show that profitability and tangibility are significant negatively related with the debt ratio. In contrast, growth is significant positively correlated with the debt ratio. However, although firm size is positively correlated with debt ratio but it is insignificant to determine the choice of capital structure. It is found that Singapore listed manufacturing firms are more to Pecking Order theory.